IMPLEMENTASI METODE BAMBOO DANCING DALAM MENINGKATKAN KEAKTIFAN BELAJAR PESERTA DIDIK PADA MATA PELAJARAN PENDIDIKAN AGAMA ISLAM DI SD SWASTA PAB 33 DESA SIDODADI KECAMATAN BIRU-BIRU - Syahfitri Rahmawardiani; Khairuddin Lubis; Hotni Sari Harahap (Fakultas Agama Islam Universitas Al Washliyah, 2025)
The aim of this research is to find out : 1. Application of the bamboo dancing method in Islamic religious education subjects at PAB 33 Sidodadi Private Elementary School, Biru-Biru District. 2. Obstacles faced by teachers when implementing the bamboo dancing method at PAB 33 S idodadi Private Elementary School, Biru-Biru District. In this research, the method the author uses is descriptive qualitative. Data collection techniques were used through observation, interviews and documentation. The data analysis techniques that the author uses are data reduction, data presentation, and data verification and drawing conclusions. The results of the research show that : 1. The bamboo dancing method in Islamic religious education subjects can be applied and well received by class V students at PAB 33 Sidodadi Private Elementary School, Biru-Biru District. 2. The obstacles experienced in implementing the bamboo dancing method are: 1) Students’ low memory in providing information to discussion partners. 2) Students disturb each other and make noise. 3) Students who are shy